Uma abordagem baseada em jogos de diálogo para gerenciamento colaborativo de riscos - Severo, Fabrício Severo de (2013)
Risk management is a set of principles and pratices which aims to identify, analyse and treat events that could happen in the development of software projects with the objective of reducing surprises and increasing the success rate of the projects. Although collaboration is important to the execution of those tasks, there has been little attention to the interaction steps of dialogues, or argumentation, which occur when those participants develop risk management discussions. This work presents a new approach, based on the argumentation theory, to the development of collaborative tasks of risk management. With grounds on "dialogue games", this approach proposes a new communication protocol tailored to the risk management needs. In particular, this protocol is defined by its locution acts and combination rules between those locutions. This way, this protocol allows the structuring and controlling of risk discussions being developed by participants in a debate. Based on the proposed protocol, this work also presents a web system - Risk Discussion System (RD system) - built to present a collaborative environment for risk discussions. Since those discussions are structured by the dialogue game, the system is responsible for the organization and the recording of those risk discussion on a memory, allowing the analysis and reuse of those discussions on future ones. Aiming to evaluate the proposed approach, together with the protocol and the system presented, two experiments were conducted in this project. Results of those experiments present positive evidence for the acceptance and applicability of the approach in risk discussions, and the increment of the quality of information that is usually managed by other kinds of strategies for risk and project management.